Effects of Complex Training on Jumping and Change of Direction Performance, and Post-Activation Performance Enhancement Response in Basketball Players - Piotr Biel; Paulina Ewertowska; Petr Stastny; Michał Krzysztofik (MDPI AG, 2023)
Exercise order is one of the significant factors modulating training effects. Therefore, the aim of this study was to compare the effectiveness of an 8-week complex (CPX) training program utilizing intra-CPX active recovery with compound training (CMP) on bilateral and single-leg jumping performance, change of direction test time (shuttle test), and the post-activation performance enhancement (PAPE) response in a group of basketball players. Thirteen participants were performing CPX bi-weekly combined with regular pre-season basketball practice, while eleven participants were performing CMP for 8 weeks. Before and after the interventions, the following fitness tests were assessed: (i) bilateral countermovement jump, (ii) single-leg countermovement jump, (iii) shuttle run test. All tests were performed pre- and post-conditioning activity (CA-three sets of five drop jumps). The results showed a statistically significant increase in non-dominant (p = 0.019) and dominant single-leg jump relative peak power (p = 0.001), and in non-dominant single-leg jump height (p = 0.022) post-training compared to pre-training. The CA was significantly and similarly effective in eliciting a PAPE response in all tests before and after each intervention (p < 0.039; for all). However, the magnitude of improvement in CMJ and shuttle test time was trivial to small and did not reach statistical significance. Both 8 weeks of CPX and CMP training led to significant improvements in the SLJ power output of both the dominant and non-dominant limbs as well as the height of the non-dominant SLJ. Neither of the training methods had significant impacts on the magnitude of the PAPE response.